2014
DOI: 10.1111/fwb.12368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warming on annual production and nutrient‐use efficiency of aquatic mosses in a high Arctic lake

Abstract: 1. Primary production in Arctic and Antarctic lakes is typically dominated by benthic photosynthetic organisms. These include aquatic mosses that can be very abundant although they must be able to tolerate extreme seasonal climatic variation in irradiance and temperature. Climate change is expected to cause increased nutrient run-off and to prolong ice and snow cover on Arctic lakes. 2. Despite the substantial role that aquatic mosses play in Arctic and Antarctic lakes, our study is the first of its kind to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Tree C:N ratio also decreased with deeper WT position, indicating that the larger TIN pools in the soils at drier sites resulted in higher N content in the overstory biomass. Our findings corroborate with those of Choi et al () and Riis et al () for strong relationships between soil TIN and vascular vegetation C:N ratios. Moss TN and C:N values also changed slightly in response to warming and short‐term drainage (very little moss was present at the longer term drained sites), but these shifts were limited.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tree C:N ratio also decreased with deeper WT position, indicating that the larger TIN pools in the soils at drier sites resulted in higher N content in the overstory biomass. Our findings corroborate with those of Choi et al () and Riis et al () for strong relationships between soil TIN and vascular vegetation C:N ratios. Moss TN and C:N values also changed slightly in response to warming and short‐term drainage (very little moss was present at the longer term drained sites), but these shifts were limited.…”
Section: Discussionsupporting
confidence: 93%
“…The magnitudes of the warming‐induced increases in extractable TIN, NO 3 , and NH 4 pools were the highest at the drained hummocks at which the highest warming‐induced productivity has been reported (Munir et al, ) and in fact nutrient pools were related to the reported productivity (ANOVA, F 1, 23 = 41.69, p < .001, R 2 = .39). This study, combined with changes in carbon exchange measured at the same site, demonstrates that warming very likely increases nutrient concentrations directly by enhancing decomposition and subsequent mineralization of peat and indirectly by accelerating nutrient cycling between the peat and vegetation as reported by previous studies (Bubier, Moore, & Bledzki, ; McGrath et al, ; Riis, Christoffersen, & Baattrup‐Pedersen, ).…”
Section: Discussionsupporting
confidence: 81%
“…Hence, the ability of eelgrass to store carbon reserves in rhizomes during the summer period of abundant light availability is critical to meet metabolic demands during the dark winter months (Zimmerman et al 1989), and probably accounts for the fact that eelgrass indeed can survive long periods of darkness under sea ice (McRoy 1969). Prolonged periods of winter darkness may, however, affect eelgrass growth negatively, as suggested by the inverse relationship between annual net production and the duration of ice cover in arctic freshwater mosses and marine macroalgae (Krause-Jensen et al 2012, Riis et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, only few direct quantitative measurements of moss primary production have been reported (Priddle 1980;Finlay and Bowden 1994), and these were reports on short-term measurements of primary production rates during summer without any attempt to scale up to annual production. Annual primary production of Arctic lake moss vegetation has been estimated using annual growth segments (Sand-Jensen et al 1999;Hawes et al 2002), also but this method relies on morphological distinct annual growth segments developing in certain moss species (Riis and Sand-Jensen 1997;Riis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from Antarctic lakes show that moss production is strongly influenced by underwater irradiance (Priddle 1980), and Riis et al (2014) showed that annual production of Drepanocladus trifarirus [Pseudocalliergon trifarium (F. Weber & D. Mohr) Loeske] growing in a High-Arctic Greenland lake was most strongly influenced by the prolongation of snow cover in summer. Most high-latitude lakes are oligotrophic, and primary production can therefore also be nutrient-limited under saturating light and inorganic carbon conditions.…”
Section: Introductionmentioning
confidence: 99%